Characterization, Phytochemical Screening and Antimicrobial Properties of stem bark extract of Theobroma cacao (Cocoa) - Olaleye, Timilehin Francis; Ogunbiyi, Oluwagbenga John (International Journal of Scientific Research in Biological Sciences, 2022)
Theobroma cacao (cocoa) is one of the medicinal plants that most of its properties is yet to be fully unravel as it is underutilized in most part of the countries. Several reports have focused on few of its uses in the area of ethno-medicine and folk medicine. The aim of this study is to characterize the phytochemical screening and antimicrobial properties of Theobroma cacao stem bark extract. The phytochemicals were extracted from dried milled stem bark of cocoa (Theobroma cacao) using solvent extraction method. The results showed the presence of alkaloids, tannins, saponins, glycosides, phenols, carboxylic acids and flavonoids. Antimicrobial acid metabolite indicates the presence of micro-organisms such as Escherichia coli, Streptococcus pneumonia, Staphylococcus aureus and Pseudomonas aeruginosa, while the neutral and basic metabolites activities indicates nil-potential towards same micro-organisms. The proximate analysis of cocoa stem bark extract was also evaluated and the antimicrobial activities of the extract were compared with standard antibiotics. PhytochemicalAntimicrobialMetabolitesCharacterization